The In Vitro Effects of Biomaterials on Lymphocyte Responses to an Allogeneic Challenge - Farooqui, Nadira (My University, 2006)
It has been shown that when implanted individually, both cells and biomaterials elicit biological responses. Implanted cells are often destroyed by the host's immune system, while biomaterials activate foreign body reactions which can result in inflammation and fibrotic encapsulation. However, when implanted simultaneously, the inflammatory responses to the biomaterial component can alter the immune responses to the cellular component. The experiments described in this thesis were designed to characterize the effect of different biomaterials on adaptive immune responses towards an allogeneic challenge. Balb/c splenocytes were challenged with irradiated allogeneic L929 cells, and treated with different biomaterials. Alterations in adaptive immune responses were quantified by T cell proliferation and cytokine release (i.e. IL-1(beta), IL-4, IL-12, and IFN-(gamma)). The roles various cell types played in first set responses were investigated. Experimental results indicated that biomaterials had a significant influence on nonspecific proliferation of splenocytes. In particular, analysis of the degree to which biomaterials affected specific proliferation indicated that the soluble alginate treatment significantly increased proliferation differences when compared to the control. However, biomaterials neither significantly affected specific splenocyte proliferation to an allogeneic challenge, nor the profile of secreted cytokines. To elucidate this response, alginate-treated splenocytes were depleted of adherent macrophages, CD4+ cells or CD8+ cells. Within non-challenged mixtures, CD4+ depletion had the most obvious effect. These results were supported by the non-depleted challenges, and indicated the direct influence biomaterials on CD4+ T cell proliferation.
Keywords: in vitro; lymphocyte; allogeneic challenge; biomaterial